FAUNA OF THE BUFFALO HELMINTHS IN THE SOUTHEAST OF THE NORTH CAUCASUS - Madina M. Zubairova; Agay M. Ataev; Nadyrsoltan T. Karsakov; Djamilya G. Kataeva; Tamila N. Ashurbekova (Юг России: экология, развитие)
Abstract. Aim. The aim is to analyze the fauna of buffalo helminths at the northern border of the European part of Russia, the extensiveness and intensity of cattle infection in pastures of different ecological types, environmental factors affecting the population size and the formation of the helminth faunistic complex of anthropogenic foci of bio and geo-helminthoses. Methods. To achieve the goal, the following methods were used: helminthoscopy, ovarioscopy and larvoscopy; technique of complete helminthological dissection of animals and humans according to K.I. Scriabin; artificial acquisition of larvae, study of mollusks, oribatid mites, flotation, successive washing of faeces. Results. A study carried out for more than 40 years has shown that the fauna of buffalo helminths is represented by 44 species, where 5 of 15 biohelminthes are of the trematode class, 7 cestodes, 3 nematodes and 29 geo-helminths (nematodes). A rich species composition (25 species) is represented by Strongylata suborder, Railliet et Henry 1913. The complex of buffalo helminthes fauna is represented by a rich biodiversity of species (44 species) on lowland moist pastures and on coastal areas flooded with freshened waters of the western shores of the North Caucasus. The formation of the complex of buffalo helminthes fauna occurs in the second and third year on the above mentioned ecological types of pastures. Conclusion. Buffalo is infected by helminths with a prevalence rate (PR) of 0.8-42.1%, with an infection intensity (II) of 2-2040 specimens. Mixed foci of helminthiases are formed on all ecological types of pastures. This is due to the fact that 93.2% of parasites are specific for ruminants. Biodiversity of species, the formation of the complex of buffalo helminthes fauna depends on the impact of environmental factors. The complex of buffalo helminthes fauna on different types of ecological pastures is represented in mixed invasions from 3 to 14 species of pathogens.